Teachers' Roles in Fostering Emotional Intelligence Development among Elementary School Students: A Qualitative Case Study - Uswatun Hasanah; Aziz Nuri Satriyawan (Al-Aulad: Journal of Islamic Primary Education, 2026)
Teachers play a crucial role in the development of students' personalities. This role is not easy because, in addition to mastering the concepts taught to students, teachers must also be able to understand student characteristics. Teachers must be able to be role models, motivators, and evaluators for students. This study aims to comprehensively examine the role of teachers in fostering and developing emotional intelligence in second-grade students at Muhammadiyah 01 Mantingan Elementary School, Ngawi. This study uses a qualitative descriptive approach, with data analysis techniques that include observation, interviews, documentation, and field notes. The subjects of the study were one second-grade teacher and 24 second-grade students. The results of this study indicate that teachers play an important role as role models in shaping students' emotional intelligence and have implemented it optimally. The teacher's role as a motivator in shaping the emotional intelligence of second-grade students has also been running optimally, as seen from the students' active participation during the learning process. In addition, the role of an educator as an evaluator during the process of developing students' emotional intelligence has also been carried out independently by second-grade students and has also been implemented quite well. The forms of students' emotional intelligence are as follows: 1) self-awareness, namely being able to understand oneself, 2) emotional management where students are able to control emotions in every situation, 3) motivation including high enthusiasm in learning, 4) empathy towards others and 5) social skills, being able to interact with teachers and friends.